The acquisition of Korean subject and complementary particles 'i/ga' among Indonesian learners - Meutia, Fitri (Universitas Pendidikan Indonesia (UPI), 2024)
Subject and complement markers 이(i)/가(ga) are markers used to form a sentence in Korean language, which are quite difficult for Indonesian Korean learners to master because in Indonesian there is no subject or complement marker. Therefore, it is difficult to conquer. This research is a descriptive quantitative study that aims to find out the acquisition of Korean subject and complement markers 이(i)/가(ga) of Indonesian Korean language learners, and difference in understanding Korean subject and complement markers 이(i)/가(ga) between native Korean speakers and Indonesian Korean language learners. Grammaticality Judment Test (GJT) and statistical tests were conducted on 60 learners of Korean learners, and 20 native Korean speakers to determine their acquisition and difference. The results found that learners acquisition was quite low as seen from the average of correct answers which was only 72 point for the highest and 45 for the lowest. In addition, it was also found that there is significant difference (Sig. 0.05) between native Korean speakers and Indonesian Korean language learners regarding understanding Korean subject and complement markers 이(i)/가(ga). The results of this study are similar to previous studieswhich found that there were significant differences between native Korean speakers and Indonesian learners in recognizing Korean subject and complement markers 이(i)/가(ga.